Suppression of sterol 12α-hydroxylase transcription by the short heterodimer partner: insights into the repression mechanism - del Castillo-Olivares, Antonio (Oxford University Press, 2001)
Cholesterol conversion to bile acids is subject to a feedback regulatory mechanism by which bile acids down-regulate their own synthesis. This regulation occurs at the level of transcription of several genes encoding enzymes in the bile acid biosynthetic pathway. One of these enzymes is sterol 12α-hydroxylase/CYP8B1 (12α-hydroxylase), the specific enzyme required for cholic acid synthesis. The levels of this enzyme determine the ratio of cholic acid to chenodeoxycholic acid and thus the hydrophobicity of the circulating bile acid pool. Previous studies from this laboratory showed that fetoprotein transcription factor (FTF) is required for 12α-hydroxylase promoter activity and bile acid-mediated regulation. Here, we report that the short heterodimer partner (SHP) suppresses 12α-hydroxylase promoter activity via an interaction with FTF. Hepatic nuclear factor-4 (HNF-4) binds and activates the 12α-hydroxylase promoter and is required for 12α-hydroxylase promoter activity. Although HNF-4 interacts with SHP, it is not involved in SHP-mediated suppression of 12α-hydroxylase promoter activity. FTF and not HNF-4 is the factor involved in regulation of 12α-hydroxylase promoter activity by bile acids through its interaction with SHP. Finally, interaction of SHP with FTF displaces FTF binding to its sites within the 12α-hydroxylase promoter. These results provide insights into the mechanism of action of bile acid-mediated regulation of sterol 12α-hydroxylase transcription.